Channel measurements, characterization, and modeling for land mobile satellite terminals in tropical regions at Ku-band - Al-Saegh, Ali M.; Sali, Aduwati; Mandeep, Jit Singh; Fontan, Fernando Perez (IEEE, 2017)
Severe tropical weather dynamics impairments on the earth-sky signal quality at the Ku-band relative to temperate weather increase the demand for land mobile satellite (LMS) channel characterization and modeling specific to tropical regions. Variation in weather dynamics decreases the accuracy of the existing LMS channel models if applied to the tropics. This paper presents a tropical weather-aware LMS channel model that can be applied at areas with diverse atmospheric (rain, clouds, and tropospheric scintillation) and mobility impairments. The proposed tropical-LMS channel (TRO-LMSC) model is designed based on actual experimental measurements conducted in a tropical area. The TRO-LMSC model involves multipath design, mobility model, rain impairment model, cloud impairment model, tropospheric scintillation model, and link budget module (LBM). The proposed model shows improved channel modeling accuracy and comprehensiveness with relatively less root mean square error (rmse), compared with existing models. Consequently, this improvement enhances the identification of the type and performance of the fade mitigation technique, the management of available communication resources, and the reliability and efficiency of the communication services.